Research trend analysis of the undergraduate theses produced under the BS Clothing Techonology program from 2006-2015 - Abenojar, Alexandra A.
The BS Clothing Technology (BSCT) program takes part in the mission of the University of the Philippines (UP) and College of Home Economics (CHE) to contribute to the development of knowledge and in addressing the needs of the family and the nation through research. This is a descriptive research wherein content analysis method was utilized. The researcher created a database and identified the trends in topics and beneficiaries of the researches produced under the BSCT program from 2006 to 2015. These trends were analyzed through the survey method using the primary sources of thesis topics of selected BSCT alumni and the influence of the Research Methods professor in topic selection. Purposive sampling was used to select the respondents of the survey. The trends showed that the prominent sources of thesis topics are Personal inclination/interest and identified Need of friends or family. These show an apparent relation to the way the Research Methods professor guides the students in thesis topic development. According to the four thrusts of the degree program, Design is the most popular thrust, while there are only few studies on Policy, Education, and Career. Researches on Design and Materials significantly increased in the latter five years, which the researcher attributes to the students creating studies on themes that they are very exposed to (Design) or not very exposed to (Materials) in the program. In light of the research themes established by the CTID department, Culture is the most prominent theme while Policies, Education, and Consumer rights are the least studied themes. There was an increase in studies produced on Environmental concerns, Sustainable design, Ethics, and Policies, possibly suggesting an increase in awareness on these topics in the recent years. In terms of beneficiaries, the studies done for the past 10 years have benefited Producers the most while studies for the academe and policy development are not very prominent. The researcher recommends that similar research be done with a wider scope in terms of the research covered, and the aspects of the research to be analyzed such as methodology, bibliography, etc.